The Influence of Financial Compensation and Competence on Employee Performance at PT Abadi Permai Medan - Helman, Helman (Syntax Corporation Indonesia, 2024)
The research object is PT. Abadi Permai Medan. The research was conducted in the company because there was a decline in the performance of the company's employees. Employee performance is the work of employees to do a job assigned to an employee. Employee performance always gets the main attention because it plays a very big role for the company's progress. Financial compensation is a form of payment of money paid by the company for employee work services in the company. The provision of financial compensation is always a consideration of employees in displaying the work they are capable of achieving. Competence is the ability possessed by employees in carrying out and supporting the work that is their responsibility. The research used several theories of human resource management related to financial compensation, competence and employee performance. The data collection was performed by interviews, questionnaires and documentation studies. The research data were drawn by using a simple random sampling technique with saturated sampling consisting of 76 permanent employees and 30 employees were derived from PT. Forsindo Jaya which were a similar type of company which were used for validity and reliability tests. Partially and simultaneously, the results of the study showed that communication and recruitment had a positive and significant effect on employee performance with a coefficient of determination of 60.5% and the remaining 39.5% can be explained by other variables not investigated in the research leadership, discipline and communications. The partial testing for the financial compensation variable was (2.647> 1.993) and the competency variable was (5.112> 1.993). In addition, the result of the F test (58.326> 3.120). Based on the results, it was concluded that financial compensation and competency had a positive and significant effect on employee performance at PT. Abadi Permai Medan